Calcium Supplementation and Bone Mineral Density in Postmenopausal Women Using Estrogen Replacement Therapy - Haines, C. J. (Institutional Knowledge at Singapore Management University, 1995)
Both estrogen and calcium have been shown to be of benefit in reducing the incidence of osteoporosis in postmenopausal women. It has been suggested that estrogen promotes the intestinal absorption of calcium, and this effect may especially benefit postmenopausal women with a low dietary intake of calcium. The purpose of this study was to examine the effect of calcium supplementation on the bone mineral density (BMD) of postmenopausal women using estrogen replacement therapy. BMD measurements were made over 12 months in two groups of postmenopausal women, one having treatment with estrogen alone, and the second having estrogen and 1000 mg of supplemental calcium each day. There was no significant reduction in BMD between the two groups over the 12-month study period. Those in the group having supplemental calcium had a significant increase in BMD at the femoral neck (p = 0.023), but not in other areas at femur nor in the lumbar spine. The results of this study suggest that the addition of supplemental calcium may improve the bone mass of postmenopausal women using estrogen who have a low dietary calcium intake. This benefit appears to be more pronounced in corticocancellous than in trabecular bone, and may therefore have a greater effect on the femoral neck than the lumbar spine.